Myopathic Blepharoptoses: A New Classification System. Issue 6 (November 2019) - Burnstine, Michael; Greer, Christine; Lee, Diana K.; Kim, Jonathan W.
Abstract : Purpose: Myopathic blepharoptoses (ptoses) is a complex group of disorders. To date, no formal categorization scheme has been developed based on associated ocular and systemic findings, genetic fingerprint, treatment, and prognosis for each ptosis in this group. We report a new classification scheme for myopathic ptoses. Methods: Literature review and classification development. Results: A new classification scheme of myopathic ptoses includes isolated static myopathic ptosis (congenital ptosis), static myopathic ptosis associated with aberrant innervation and those associated with periocular abnormalities, and progressive myopathic ptoses that affect the levator muscle and other muscle groups in childhood and adulthood. Conclusions: Making the distinction of myopathic ptosis type early will maximize patient outcomes by optimizing surgical and systemic management and facilitating the recruitment of subspecialists to care for patients with these challenging conditions. The authors present a comprehensive and effective myopathic ptosis classification scheme to optimize surgical management and facilitate subspecialty care.